Pendampingan Strategi Instagram Ads Berbasis Analisis Engagement dan Pola Psikologis Orang Tua pada Daycare - Khusnuliawati, Hardika; Musslifah, Anniez Rachmawati; Cahyani, Rusnandari Retno (Universitas Muhammadiyah Mataram, 2026)
Abstract: Digital promotion in early childhood education institutions is often conducted intuitively without data analysis and audience behavior insights, leading to suboptimal Instagram Ads performance. This issue was also identified at Al Ghazi Daycare. This community service program aimed to provide assistance in developing Instagram Ads strategies based on engagement analysis and parents’ psychological patterns to improve digital promotion effectiveness. A participatory training and mentoring approach was applied, including needs assessment, training on Instagram Insights and Meta Business Suite, content and posting schedule design, as well as ad implementation and evaluation. The results show improved managerial skills in handling data-driven Instagram Ads, accompanied by increased digital interaction and enrollment interest during the advertising period. This program demonstrates that combining engagement analytics with audience psychological insights can support effective and sustainable daycare promotion.Abstrak: Promosi digital pada lembaga pendidikan anak usia dini masih sering dilakukan secara intuitif tanpa analisis data dan pemahaman perilaku audiens, sehingga efektivitas Instagram Ads belum optimal. Permasalahan tersebut juga dialami oleh Al Ghazi Daycare dalam pengelolaan promosi digitalnya. Kegiatan pengabdian masyarakat ini bertujuan memberikan pendampingan strategi Instagram Ads berbasis analisis engagement dan pola psikologis orang tua untuk meningkatkan efektivitas promosi daycare. Metode yang digunakan adalah pelatihan dan pendampingan partisipatif melalui identifikasi kebutuhan mitra, pelatihan penggunaan Instagram Insights dan Meta Business Suite, perancangan konten dan jadwal posting, serta implementasi dan evaluasi iklan. Hasil kegiatan menunjukkan peningkatan kemampuan pengelola daycare dalam mengelola Instagram Ads secara lebih terarah dan berbasis data, disertai peningkatan interaksi digital dan minat pendaftaran peserta didik selama periode iklan. Pendampingan ini membuktikan bahwa pendekatan berbasis data dan psikologi audiens efektif mendukung promosi daycare secara berkelanjutan.